Analisis Penggunaan Rele Jarak Pada Sistem Transmisi Gardu Induk 150 kV Jajar Ke Gardu Induk 150 kV Banyudono - Mu'tashim, Qoid Zuhdi, Umar, S.T. M.T (2017)
Transmission line connects generation with substation or in between substation. The main purpose for transmission line is to distribute electricity from generation for use in various faraway places. Protection on the transmission line has a very important role in the electric power systems. Safety relay is a planned series of safety equipment to detect an abnormality on the condition of electrical equipment. Distance relay works by measuring the amount of fault impedance (Z) transmission, and compare it with setting's impedance in the distance relay, divided into few zone, there are zone 1, zone 2, and zone 3. The use of distance relay on system High Voltage Overhead Transmission (HVOT) 150 kV's network, is expected to help the reliability of the transmission system. The method that is used to determine the value of setting distance relay on the HVOT 150 kV Jajar substation - Banyudono substation is finding the parameter data for the station, transformer, and transmission wire. The new calculated value of distance relay, used and simulated in the network, wheter it can work proportionally and accurately. The calculated value of reach impedance based on the transmission wire data are as such: zone 1 : (2.199+j3.987) Ω, zone 2 : (4.31+j7.814) Ω, zone 3 : (7.26+j13.156) Ω